A new genus and species of the family Microdispidae (Acari: Heterostigmata) associated with Trinervitermes trinervoides (Sjöstedt) (Isoptera: Termitidae) from South Africa - Khaustov, Alexander A.; Hugo-Coetzee, Elizabeth A.; Ermilov, Sergey G.; Theron, Pieter D. (Zootaxa, 2019)
A new genus and species of termitophilous microdispid mites, Sidorchukdispus ekaterinae gen. nov. and sp. nov. (Acari: Prostigmata: Microdispidae), associated with termites, Trinervitermes trinervoides (Sjöstedt) (Isoptera: Termitidae) are described from South Africa. The morphological and biological traits of Sidorchukdispus ekaterinae gen. nov. and sp. nov. are discussed.